La enseñanza de la filosofía - Calcín Figueroa, Eduardo (2011)
Taking into account a family experience, this article pretends to analyze Philosophy teaching and the so well discussed “importance” to learn it, having Socrates and Plato as great learning and philosophy teaching's methodologists. The author is based on the principle that professor should first love what he teaches, following and guiding the student during the learning process where it constructs its own knowledge, because even though there are no methods to teach and think, the teaching attitude leads the encounter, as well as the enjoy for learning.